Psychological Tests in Selection of Students to Schools of Nursing in Israel - A. Rotenberg (AOSIS, 1978)
Psychological tests as one of the influential and, in some instances, crucial criteria in selecting candidates to schools of nursing, have long been used and during the last 25 years have been discussed in literature.